STUDENTS’ DIFFICULTIES IN LEARNING SPEAKING AT THE UNIVERSITY LEVEL: AN ANALYSIS OF CONTRIBUTING FACTORS - Argawati, Ningtyas Orilina; Musthafa, Bachrudin; Gustine, Gin Gin (Universitas Islam Sumatera Utara (UISU), 2025)
Mastering speaking as a crucial ability for language learners seems to be challenging. Students had challenges in acquiring this ability. Teachers claimed that the challenges stemmed from students' apprehension or lack of desire. Teachers must identify the underlying issues that hinder learning to effectively address the problems they face. This qualitative research examined the main variables that prevent university students from developing English-speaking abilities. Data were assessed through classroom observation of one class of the first semester of university-level consisting of 42 students, and interviews with 12 chosen participants, focusing on five major characteristics of speaking: pronunciation, grammar, vocabulary, fluency, and comprehension. Research findings indicate that pronunciation errors, grammatical mistakes, limited vocabulary and expression, fluency and Speech Rhythm Issues, and Comprehension and Responsiveness Challenges were significant factors which contributed to the difficulties faced by students. Findings may inform pedagogical approaches to enhance speaking performance. Furthermore, the result of the data can be used by students and teachers to arrange some plans to overcome the difficulties.